Guanxinshutong Alleviates Atherosclerosis by Suppressing Oxidative Stress and Proinflammation in ApoE−/− Mice. (16th September 2020) - Lu, Yingdong; Sun, Yuchan; Jiang, Zhilin; Zhang, Dandan; Lin, Hongchen; Qu, Yi; Shang, Chang; Zhao, Mingjing; Cui, Xiangning
Abstract : Atherosclerosis (AS) is a chronic progressive disease related to dyslipidemia, inflammation, and oxidative stress. Guanxinshutong capsule (GXST), a traditional Chinese medicine, has been widely used in treating coronary atherosclerotic heart disease, while its mechanism actions on AS are still not to be well addressed. Our present study is aimed to examine the effect of GXST on AS and elucidate the multitarget mechanisms of GXST on AS. Network pharmacology analysis was employed to screen the multitarget mechanisms of GXST on AS. ApoE −/− mice were used to validate these effects. Circulating lipid profile and oxidative stress-related factors were measured by the Elisa kit. Furthermore, the aortic trunk and aortic root were excised for oil red O staining, histopathological and immunohistochemical analysis. We first discovered that GXST was clued to exert synergistically antiatherosclerosis properties including lipid-lowering, anti-inflammation, and antioxidation through the computational prediction based on a network pharmacology simulation. Next, the validation experiments in atherosclerosis mice provided evidence that GXST significantly reduced atherosclerotic lesions, increased collagen deposition, and attenuated LV remodeling to some extent. Mechanistically, GXST modulated lipid profile, downregulated the level of inflammatory cytokines and NF- κ Bp65. GXST also reduced the activity of oxidative parameter MDA and upregulated the activities of antioxidant enzymes (SOD and GSH) compared with the AS model group. In conclusion, GXST intervention might attenuate atherosclerosis by mechanisms involving reducing lipid deposition, modulating oxidative stress and inflammatory responses, but a larger controlled trial is necessary for confirmation.